FLEXIBLE MANAGEMENT OF COSTS, PROFITS AND PRICES USING TARGETED PLANNING - ORLOV, OLIVER; RYASNYKH, EYHENIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Under market conditions, the main feature of enterprises is the focus on consumer demand, the desire for innovation, the implementation of appropriate scientific and technical innovation policy. Flexibility in management, the ability to restructure quickly without losing new opportunities can be more important than just cost savings.The high degree of uncertainty, which is characteristic of modern conditions of economic development, requires the use of flexible planning tools that allow you to quickly take into account changes in supply and demand, requirements for product quality, prices, etc.In the conditions of competition between producers and the need to improve their economic performance and, above all, profit, employees must have economic tools that would allow them to consider different options for prices, costs, scale of production, changes in the structure of its range and to monitor the consequences of these changes in the economy of the enterprise. One such tool is targeted planning of prices, costs and profits. It is believed that the methodology of target pricing and calculation of target costs was developed in Japan and it is based on a given level of price and profit. The difference between the target price and the target profit is the target cost. But this technology does not work in terms of multi-item production.The problem of the need for flexible management of costs, profits and prices in market conditions is outlining. On the basis of theoretical and empirical researches the critical analysis of foreign scientists’ points of view to the problem of “target profit” planning and "target prime cost" is given. As authors believe the latter are possible only for single-product manufacturing companies. It is suggested to form a flexible system of targeted planning suitable for multi-product companies on the basis of the fixed costs’ distribution in proportion to the marginal profit.
Keywords: marginal profit; marginal profit ratio; parget price; break-even ratio; safety margin